Evaluating Claim Settlement in Islamic Life Insurance through the Lens of Maqasid al-Shariah: Evidence Insurance Compnay in Central Java Branch - Intan Shaferi; Hesti Widianti; Muliasari Pinilih (Journal of International Islamic Business Studies, 2025)
This study aims to evaluate the claim settlement process of the Brilliance Hasanah Sejahtera life insurance product at PT Asuransi XXX, Central Java Branch, through the lens of Maqasid al-Shariah. Employing a qualitative descriptive method, the research examines whether the operational mechanisms of Islamic life insurance claims reflect Shariah compliance and contribute to social welfare (maslahah). Data were collected through interviews, observations, and documentation from both company representatives and policyholders. The findings reveal that the claim settlement procedure—comprising claim notification, submission of documents, verification, and payment—has been implemented in accordance with Islamic principles, emphasizing transparency, fairness, and efficiency. The analysis identifies that PT Asuransi XXX embodies the objectives of Maqasid al-Shariah primarily through the dimension of hifzh al-mal (protection of wealth), while simultaneously supporting other objectives such as hifzh al-din, hifzh al-nafs, hifzh al-aql, and hifzh al-nasl. The study concludes that the company’s claim settlement process reflects the realization of dharuriyat (essential needs), promoting justice and trust in Islamic financial services.